2022
DOI: 10.21203/rs.3.rs-1841683/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Study on Dynamic Mechanical Properties of Bedding Shale Under Impact Load

Abstract: In the actual mining process of shale gas, the loads and disturbances imposed on shale by man-made activities are a dynamic process. Therefore, the study of the dynamic constitutive theory of bedding shale under impact load has important theoretical value for the study of fracturing reformation of shale reservoirs and shale gas production. The objective is to explore the dynamic mechanical properties and fracture characteristics of shale with different bedding dip angles under medium and high strain rate loadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…They observed that both uniaxial compressive strength and triaxial compressive strength were minimal when β = 60 °. Chen et al [6] studied the anisotropy of the black shale in the Niutitang Formation of the Lower Cambrian. They conjectured that the bedding angle of the shale with the minimum uniaxial compressive strength is 60 °when the confining pressure of the shale is 0, 30, and 40 MPa, and that of the shale with the minimum compressive strength is 45 °at 10 and 20 MPa.…”
Section: Anisotropy Analysis Of Stress-strainmentioning
confidence: 99%
See 2 more Smart Citations
“…They observed that both uniaxial compressive strength and triaxial compressive strength were minimal when β = 60 °. Chen et al [6] studied the anisotropy of the black shale in the Niutitang Formation of the Lower Cambrian. They conjectured that the bedding angle of the shale with the minimum uniaxial compressive strength is 60 °when the confining pressure of the shale is 0, 30, and 40 MPa, and that of the shale with the minimum compressive strength is 45 °at 10 and 20 MPa.…”
Section: Anisotropy Analysis Of Stress-strainmentioning
confidence: 99%
“…In the process of shale deposition and diagenesis, the mineral type and content, sedimentary environment, and sedimentary tectonic history of rocks [5] cause large differences in the acoustic and mechanical parameters of shale across regions. In addition, within the same region, the characteristics and occurrence of shale may differ substantially [6][7][8]. Currently, research on the anisotropy of the Longmaxi Formation shale mainly entails stress-strain curves, fracture type evaluation, and acoustic velocity determination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation